Navigating the challenges of clinical trial professionals in the healthcare sector - Peralta, Galo; Sánchez-Santiago, Blanca (Frontiers in Medicine, 2024)
Clinical trials (CTs) are essential for medical advancements but face significant challenges, particularly in professional training and role clarity. Principal investigators, clinical research coordinators (CRCs), nurses, clinical trial pharmacists, and monitors are key players. Each faces unique challenges, such as maintaining protocol compliance, managing investigational products, and ensuring data integrity. Clinical trials' complexity and evolving nature demand specialized and ongoing training for these professionals. Addressing these challenges requires clear role delineation, continuous professional development, and supportive workplace environments to improve retention and trial outcomes. Enhanced training programs and a collaborative approach are essential for the successful conduct of clinical trials and the advancement of medical research.